Increasing flooding frequency alters soil microbial communities and functions under laboratory conditions. Issue 1 (7th November 2017) - Randle‐Boggis, Richard J.; Ashton, Peter D.; Helgason, Thorunn
Abstract: The impacts of increased flooding frequency on soil microbial communities and potential functions, in line with predicted environmental changes, were investigated in a laboratory‐controlled environment. More frequent flooding events altered microbial community composition and significantly increased the resolved species alpha‐diversity (Shannon index). The Bacteria:Archaea ratio was greater at the end of the experiment than at the start, more‐so after only one flood. Significant changes in taxa and functional gene abundances were identified and quantified. These include genes related to the reduction and oxidation of substances associated with anoxia, for example, those involved in nitrogen and sulfur cycling. No significant changes were observed in the methanogenesis pathway, another function associated with anoxia and which contributes to the emission of greenhouse gases. Abstract : Increasing flooding frequency under laboratory conditions significantly altered soil microbial communities and their potential functions. This provides an insight into the response of microbial communities to future environmental conditions.